PATHOLOGICAL CHANGES OF THE MUCOUS LAYER OF THE ORAL CAVITY, MORPHOLOGICAL ELEMENTS OF DAMAGE (Academia Science Repository, 2023)
Physiology of the oral cavity of the mouth participates in tasks such as chewing and digesting food, breathing, speaking, and protecting the body from the effects of the external environment. There are 6 different senses in the oral cavity: 1) sense of taste; 2) pain; 3) cold; 4) hot; 5) touch; 6) muscle